Analisis Criminal Profiling Terhadap Pelaku Pembunuhan Berencana Berbasis General Theory Of Crime - Pascal Caya Khrisna Wicaksana; Lucky Nurhadiyanto (LPPM Universitas Ekasakti Padang, 2024)
Criminal Profiling is a method of investigating criminal phenomena. Criminal profiling involves creating a criminal profile to determine the background of the perpetrator. Premeditated murder is a heinous crime because the manner in which the perpetrator commits the murder requires planning. This plan includes what items to use, when, the right opportunity to do so, and how to escape. Therefore, this research discusses the role of criminal profiling of premeditated murder offenders in Indonesia based on the General Theory of Crime. The theory used will discuss 3 important points of the theory, namely implusive, low self-control, and opportunity. This study collects 5 examples of premeditated murder cases to be studied and presents the results of profiling the perpetrators based on the results of press conferences held by the police and summaries of several news articles. The profiles observed include the perpetrators' motives, modus operandi, socio-cultural conditions, and demographics. The method used in this research is a systematic literature review; this method requires researchers to collect and select articles, books and magazines related to this research. In addition to journal articles and books, researchers also collected references to newspaper articles to explore the development of these cases.